Drinking motives as mediator in the relationship between social anxiety and alcohol use among private university students in the Klang Valley - Raj, Sharivini Lekha A/P Youva (2016)
As social anxiety becomes a threat, drinking alcohol becomes a trend in experiencing relaxation, acceptance and decreases performance fear. Alcohol use continues to be a major concern among people within the age group 15 – 29, particularly first year university students. This thesis sought to assist in integrating a detailed analysis of potential unique mediator of alcohol use among socially anxious people through a quantitative study among 600 private university students in the Klang Valley using Social Interaction Anxiety Scale, Alcohol Use Disorders Identification Test and Drinking Motive Questionnaires-Revised. Coping and conformity motives were hypothesized to be the most significant mediator in the relationship between social anxiety and alcohol use. By examining the beta weights, coping motives (β = .27, p < .001) followed by conformity motives (β = .13, p < .05) were making relatively large contributions to the prediction model, followed by social anxiety (β = .15, p < .01) while controlling the mediators. Students with high social anxiety endorsed greater negative reinforcing drinking motives (coping, conformity) which independently mediated the relation between the two variables studied; in which the coping motives were believed to lead to adverse long-term consequences because the discrepancies that foster negative affects have never been adequately addressed